As condições sanitárias da produção de polpa de açaí associada à doença de chagas, na comunidade do rio Costa Maratauíra, Abaetetuba, Pará - CARNEIRO, Elieida do Rêgo (2019)
Chagas disease is considered as an anthropozoonosis because it is a result of environmental changes produced by man mainly affects neglected populations. In the State of Pará the most common form of contamination is oral, in the form of outbreaks or isolated cases. The objective of this work was to raise awareness among residents of the community of Nazaré-Costa Maratauíra regarding the risk factors for contamination of açaí pulp by T. cruzi during the extraction and consumption of this product. The data collection took place during the development of an educational action in the community of Nazaré-Costa Maratauíra that consisted of three visits to each family with the objective of talking about the hygiene measures that must be adopted during the manipulation and the extraction process, storage and consumption of the açaí pulp. In this research participated 70 families, composed of a maximum of nine people, being 89% female and 11% male. The age range ranged from five to 70 years of age and only 3% did not attend school. Factors such as the size of the protozoa, the presence of the barber vector of the DC in nature, the consumption of the acai pulp as part of their life histories and the abundance of the product contribute to create a state of unconcern as the hygienic measures able to eliminate the T. cruzi. Therefore, it is of fundamental importance the investment of the public power so that informative and enlightening activities are developed through the school and the community's ACS in the combat and prevention of diseases, as in this case the DC.